A study of complications in case of unicornuate uterus with rudimentary horn - Kamal, Samarina; Roy, Priyankur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To analyse gynecological and reproductive morbidities associated with unicornuate uterus with noncommunicating rudimentary horn. Methods: This is a retrospective study of 20 cases of unicornuate uterus with noncommunicating rudimentary horn found on laparotomy in a duration of 5 years (Oct 2011-Oct 2016). Results: Out of 20 patients, two teenagers presented with dysmenorrhoea and pain abdomen and had haematometra in the noncommunicating rudimentary horn which was excised. Eight had pregnancy in the noncommunicating rudimentary horn of which all presented after rupture and five were admitted in a state of shock. Ten patients had pregnancy in the hemiuterus with complications inherent to the condition. Conclusions: Unicornuate uterus with noncommunicating rudimentary horn is associated with poorest outcomes among all uterine anomalies and a high index of suspicion is needed to diagnose this condition and thus to save the woman from catastrophic complications.